Operative Outcomes for Cervical Myelopathy and Radiculopathy. (20th October 2011) - Galbraith, J. G.; Butler, J. S.; Dolan, A. M.; O'Byrne, J. M.
Abstract : Cervical spondylotic myelopathy and radiculopathy are common disorders which can lead to significant clinical morbidity. Conservative management, such as physical therapy, cervical immobilisation, or anti-inflammatory medications, is the preferred and often only required intervention. Surgical intervention is reserved for those patients who have intractable pain or progressive neurological symptoms. The goals of surgical treatment are decompression of the spinal cord and nerve roots and deformity prevention by maintaining or supplementing spinal stability and alleviating pain. Numerous surgical techniques exist to alleviate symptoms, which are achieved through anterior, posterior, or circumferential approaches. Under most circumstances, one approach will produce optimal results. It is important that the surgical plan is tailored to address each individual's unique clinical circumstance. The objective of this paper is to analyse the major surgical treatment options for cervical myelopathy and radiculopathy focusing on outcomes and complications.